Encyclopedia of Russian & Slavic myth and legend - Dixon-Kennedy, Mike 1958- (Santa Barbara, Calif. ABC-CLIO, 1998)
Covers the myths and legends of the Russian Empire at its greatest extent as well as other Slavic people and countries. Includes historical, geographical, and biographical background information.
Includes bibliographical references (p. 327-330) and index.
Keywords: Mythology, Slavic -- Juvenile literature; Mythology, Slavic; Mythology -- Encyclopedias